Species density and shell morphology of gold ring cowry (Monetaria annulus, Linnaeus, 1758) (Mollusca: Gastropoda: Cypraeidae) in the coastal waters of Ambon Island, Indonesia - LOUVENSKA N. LATUPEIRISSA; FREDY LEIWAKABESSY; Dominggus - Rumahlatu (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Latupeirissa LN, Leiwakabessy F, Rumahlatu D. 2020. Species density and shell morphology of gold ring cowry (Monetaria annulus, Linnaeus, 1758) (Mollusca: Gastropoda: Cypraeidae) in the coastal waters of Ambon Island, Indonesia. Biodiversitas 21: 1391-1400. The purpose of this research was to examine environmental factors, species density, and the shell morphology of Monetaria annulus. The samples were collected by using the line transect method at 6 research stations. The data of the environmental factors (temperature, salinity, and pH of seawater) as well as species density of M. annulus were collected with in-situ technique, while the shell morphology of M. annulus was measured at Laboratory of the Deep-Sea Research Center, Indonesian Institute of Sciences (LIPI) Ambon. The results of the measurements of the environmental factors in the coastal waters of Ambon Island showed some fluctuations in the measurement values. The seawater temperature ranged between 29.78-30.05 ºC, the salinity of seawater ranged from 32.12-32.33‰, and the pH of the seawater ranged from 8.34-8.49. The density of M. annulus at the research stations from the highest to the lowest was at Tanjung Tiram station, Suli station, Seri station, Hutumuri station, Halong station, and Latuhalat station (0.27 > 0.24 > 0.23 > 0.19 > 0.14 > 0.12 ind/m2). The results of the measurement of the shell morphology showed many variations in the size and shape of the shell of M. annulus with a total number (N) of 294 individuals. The length, the width, and the height of the shell, the length of the blotches, the width of the blotches, and the total weight of M. annulus from each research station were significantly different (p<0.005). These results indicate that the differences in the shell morphology of M. annulus at each research station were influenced by waves, the strength of the currents sea waves, and the different substrate of water. In addition, the variation of shell morphology can be a reason for characterization in the taxonomy of the Cypraeidae family.